Evaluasi Sistem Distribusi Air Bersih Zona Rumah Pompa Pradah Kota Surabaya - Hafsari, Vinda; Haribowo, Riyanto; Ismoyo, M. Janu (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Pradah Pump House functioned as a clean water distribution lane in one of Surabaya City zones, which goes towards customers directly. This study aims to figure out the existing condition and developing condition of Pradah Pump House’s clean water distribution in terms of water availability, hydraulics, water quality, and fire extinguishing wells condition. Simulation method by using WaterCADv8i software. In the existing condition, the aspect of water availability had a deficit of 282 l/s, pressure condition in 100% peak hour became insufficient, velocity condition of 49.45% did not meet the criteria, headloss gradient of 13% became insufficient, and the water quality condition in the furthest did not meet the requirement. In developing conditions, the study continues with adding one pump and 31 parallel pipes simulated in WaterCADv8i software with three conditions, i.e., reducing customer water supplies standards, doing a rotation of water distribution, and reducing customer coverage area. These simulations show that the average pressure score is 0.5-10 atm, velocity 0.3-6 m/s, headloss gradient 0-15 m/km, and the fire extinguishing wells’ simulation indicates that the average results of the well did not replenish at 12:00-16:00.